OPTIMASI PROSES WINTERIZING OLEIC ACID DENGAN MENGGUNAKAN METODE RESPONSE SURFACE - Hazimah - Hazimah; Evanto Ginting (Universitas Putera Batam, 2017)
Winterizing is a limited form separation of saturated fatty acids and unsaturated fatty acids, to remove wax and fat has a higher boiling point. To obtain the product specifications, parameters must be control is cloud point ≤ 7 oC. Response surface method use as a tool to determine the optimum operating conditions in the process of winterizing, the control parameter C16 feed composition, temperature, time. Feed C16 varied 19%, 20%, 21%, temperature varied 10 oC, 10 oC, 11 °C, time varied 14 hours, 14,5 hours, 15 hours for order I and central composite disgn in order II. The results showed feed C16 and temperature are significantly influence the cloud point. Model is Y = 6.920 + 1,429X1 0,636X2 + 1,030X22 1,080X12 - 0,650X1X2. Winterizing process optimization point C16 feed obtained 19.20% and temperature 9.93 oC.